Igreja e direito canônico : a dimensão jurídica do mistério da Igreja - Steffen, Carlos José Monteiro (2014)
Research of ecclesial law. The aim is to gather, analyze and interpret informations about the relationship between church and canon law. Bibliographic methodology is used. The understanding of ecclesial law is based in two pillars: the conception of Church and the concept of law. The beginning point is the new ecclesial perception manifested at the Vatican Council II. The privileged optic is the one of the legal realism. Law understood as justice object. The structure of the dissertation comprises three parts. The first comprises ecclesiological elements of the dogmatic Constitution Lumen Gentium. It privileges notions of sacrament and of communio. The second presents the principal currents of canonic law in the actual context: the theological, the pastoral and the juridicial. The third compares canon law, seen as that which is just in the church, Christ body, temple of the Holy Spirit, people of God. The research finishes with an exposition about the epistemological statute of the canonic science. The diversity of approaches from the different schools of canonic law is an expression of a healthy liberty in theological research. Its approaches are complementary. The theological dimension of canonic science allows the canonist meet demands of ecclesial justice beginning with Revelation data received through the faith light and misinterpreted by the conciliation teaching. Using the concept of law, in agreement with the judicial realism and the ecclesiology of the Vatican Council II, it is possible to overcome the conception that Church and canonic law are realities conversely extrinsic.